Upaya Adaptasi Perubahan Iklim Menggunakan Lubang Resapan Biopori dalam Meningkatkan Durasi Resapan Air Hujan di RW 01 Banjarsugihan - Anindita Berliana Puspitasari; Raden Kokoh Haryo Putro (Jurnal Serambi Engineering, 2024)
The city of Surabaya is located downstream of the Brantas River, which is an area of overflow from passing rivers, making it prone to flooding during the rainy season. Climate change is the occurrence of changes in climate components due to global warming. The vulnerability of RW 01 Banjar Sugihan is facing the problem of flooding from other higher areas. The aim of this research is to analyse the duration of rainwater infiltration and also to calculate water infiltration in flood prone areas. Biopore absorption holes (LRB) are a suitable technology that is easy to implement, cheap and environmentally friendly. Rainwater infiltration can be calculated using water infiltration through biopore holes. The results of the water infiltration calculations show that the total volume of rainwater infiltration increases with the increase in the number of biopore infiltration holes each year, until in 2024, with a total of 86 biopore infiltration holes, the volume of rainwater infiltration is 0.47 litres/second.